Elacestrant in Combination with Everolimus for Estrogen Receptor-Positive, HER2-Negative Previously Treated Advanced Breast Cancer: Results from ELEVATE - Hope S. Rugo; Sara M. Tolaney; Nancy Chan; Giuliano Borges; Rinat Yerushalmi; Marina N. Sharifi; Wassim McHayleh; Thaddeus Beck; Neelima Vidula; Erika Hamilton; Kristine J. Rinn; Joyce O'Shaughnessy; et al. (Clinical Cancer Research, 2026)
Abstract Purpose: Treatment options for progression on first-line endocrine therapy (ET)+CDK4/6i for ER-positive/HER2-negative (ER+/HER2-) advanced breast cancer (ABC) include ET plus targeted agents (CDK4/6i or PI3K/AKT/mTOR-pathway inhibitors). Elacestrant is the first single-agent oral SERD that significantly improved progression-free survival (PFS) versus standard-of-care ET in ESR1-mutated and overall ER+/HER2- ABC populations. Patients and Methods: This phase 1b/2, umbrella trial enrolled patients with ER+/HER2- ABC who received 1-2 lines of ET+CDK4/6i (including prior fulvestrant and primary endocrine resistance) and no prior chemotherapy for ABC. Patients received elacestrant with everolimus, alpelisib, capivasertib, abemaciclib, ribociclib, or palbociclib. We evaluated PFS of elacestrant plus everolimus. Results: In phase 1b (n=23), the optimal RP2D was determined as elacestrant 345 mg plus everolimus 7.5 mg. The phase 2 patient population (n=50) included: 100% prior CDK4/6i, 50% prior fulvestrant, 72% visceral metastasis, 20% primary endocrine resistance, 42% ESR1mut, 50% PIK3CAmut. Median PFS was 8.3 months (95% CI:4.0-10.2) in all patients; 8.3 months (95% CI:3.5-12.9) in ESR1mut, 9.0 months (95% CI:4.2-12.7) in ESR1wt, 8.3 months (95% CI:3.6-10.2) in PIK3CAmut, and 9.4 months (95% CI:4.0-NR) in PIK3CAwt. Adverse events (AEs) were consistent with known safety of everolimus plus SOC ET. Most common AEs were grade 1-2. Any AE leading to drug withdrawal or dose reduction was 6% and 2%, respectively. Conclusions: Elacestrant plus everolimus showed a clinically meaningful PFS benefit across clinical/genomic subgroups, irrespective of ESR1 or PIK3CA-mutation status. Elacestrant has the potential to become an ET backbone for combinations to inhibit the PI3K/AKT/mTOR-pathway with everolimus as a promising all-oral treatment.